Differences between suicide attempters and non-attempters in depressed older patients: Depression severity, white matter lesions, and cognitive functioning - Sachs-Ericsson, Natalie (2013)
OBJECTIVES: Older adults with major depressive disorder (MDD) have the highest population-rate of suicide. White matter brain lesions (WML) are a potential biological marker for suicidality in young and middle-age adults and are correlated with cognitive impairment (CI) in older adults. In the current study of older patients with MDD, we examined 1) if a history of suicide attempts was associated with a more severe course of MDD; 2) if WML are a biological marker for suicide; and 3) if suicide attempt history is associated with CI mediated by WML. SETTING: Data from the Neurocognitive Outcomes of Depression in the Elderly. PARTICIPANTS: Depressed patients (60+) who had ever attempted suicide (n=23) were compared to depressed patients (60+) who had not attempted suicide (n=223). MEASUREMENTS: Baseline and follow-up assessments were obtained for depressive symptoms (every 3 months) and cognitive functioning (every six months) over two years. Three MRI scans were conducted. RESULTS: At baseline, suicide attempters reported more severe past and present symptoms (e.g., depressive symptoms, current suicidal thoughts, psychotic symptoms, earlier age of onset, and more lifetime episodes) than non-attempters. Suicide attempters had more left WML at baseline, and suicide attempt history predicted a greater growth in both left and right WML. WML predicted cognitive decline; nonetheless, history of suicide attempt was unrelated to cognitive functioning. CONCLUSIONS: Severity of depressive symptoms and WML are associated with suicide attempts in geriatric depressed patients. Suicide attempts predicted neurological changes, which may contribute to poorer long-term outcomes in elder attempters.